Wildfire : grassroots revolts in Israel in the post-socialist era - Lehman-Wilzig, Sam N. (State University of New York Press, 1992)
Annotation Lehman-Wilzig (political studies, Bar-Ilan U.) describes Israeli grassroots extra-parliamentarianism and analyzes the impact of the most important alternative systems: illegal settlement activity, a huge underground economy, pirate cable TV stations, Black medicine, anti-religious as well as anti-secular activity, and a growing demand for electoral reform and constitutionalization of the Israeli polity. Paper edition (unseen), $12.95. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Political participation -- Israel.; Israel -- Politics and government.; Israel -- Social conditions.; Participation politique -- Israël.; Israël -- Politique et gouvernement.; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights.; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights.; Political participation; Politics and government; Social conditions; Israel